Toward a “Religious Cosmopolitanism” in the Age of Globalization - Yoo, Yun Kwon (Interreligious Studies and Intercultural Theology, 2022)
This article reflects critically on cosmopolitanism in our contemporary context of globalization. It examines whether cosmopolitanism can serve as an adequate anthropological perspective that responds sufficiently to the challenges of globalization, particularly in its economic, political, and cultural dimensions. Cosmopolitan anthropology is relevant and necessary in the age of globalization in that the critical challenge posed by today’s globalizing world is not only how to recognize differences per se but also, and more importantly, how to live together with all these differences. This requires our cosmopolitan awareness that we all are fellow human beings. This paper argues, however, that cosmopolitanism needs to be sublated into a religious cosmopolitanism by incorporating a theological anthropology that provides a more full-blown conception of being human as a concrete totality of all its constitutive relations whose ultimate source is God.